When Is an Audit “Good Enough”? Professional Ambiguity and Strategic Sensemaking During an Audit Oversight Inspection - Groot, Wendy; Detzen, Dominic; Gold, Anna (Contemporary Accounting Research, 2026)
ABSTRACT This paper draws on the social control and sensemaking literatures to study how a Big 4 audit firm in the Netherlands sought to contest the national oversight body's inspection findings on one of its audit engagements. Our case study leads us to develop the concept of professional ambiguity to capture the multiple, coexisting meanings and interpretations of audit evidence and professional judgment inherent in audit work. We show how professional ambiguity creates a space for discursive struggles between auditors and inspectors, enabling audit firms to engage in strategic sensemaking aimed at contesting looming inspection findings. In our case, this process entailed the mobilization of senior firm actors who reinterpreted the focal engagement as broadly acceptable—or “good enough.” Yet, when enacting this pragmatic reframing, the firm ultimately failed to overturn the oversight body's findings. Despite this outcome, we argue that audit firms seek to mobilize professional ambiguity and engage in strategic sensemaking to reshape oversight bodies' interpretations of audit engagements in inspection processes.